FACTORS INFLUENCING MILK PRODUCTION OF LOCAL GOATS OF ROHILKHAND REGION OF UTTAR PRADESH UNDER SEMI INTENSIVE SYSTEM* (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the effect of season, parity, type of birth and teat abnormality on milk yield of local goats of Rohilkhand region. A total of 32 does were selected for the experiment, and were grouped according to season (rainy and winter), parity (primiparous and multiparous), type of birth (single and twin), and type of teat abnormality (normal teat and abnormal teat). All does were milked twice daily and milk yield was recorded up to 90 days. It was found that average daily milk yield (ADMY) and total milk yield of 90 days (TMY) were significantly (P
Keywords: Goat milk; Parity; Season; Teat abnormality